Earnings Transitions of the Low-Paid in Britain, 1976-91: A Longitudinal Study. - Gregory, M; Elias, P (1994)
Using a large panel of employees from the New Earnings Survey, examines the subsequent earnings transitions of those who were in the lowest quintile of the earnings distribution in 1976. Traces the quintile earnings positions in 1984 and 1991 of three age groups of 1976--the young, the prime-aged, and older workers. Presents and analyses transition probabilities for each group, and contrasts the experience of men and women in terms of the incidence of low pay and its persistence. Also examines the previous locations within the earnings distribution of those who were low paid in 1991.